PENCIPTAAN DESAIN KEBAYA BERGAYA FUNKY BERTEMA “ KEBAYA AROUND THE WORLD “ DENGAN INSPIRASI BAR JACKET - Kuncoro, Argi Dwi; Arifiana, Deny (Universitas Negeri Surabaya, 2024)
The aim of this research is, among other things, to describe the process and results of creating a funky style kebaya design with the theme